Factors affecting digital transformation of insurance in the Republic of Serbia - Jovica Stanković; Jelena Stanković; Zoran Tomić (Economic Themes, 2022)
Implementation of IT innovations in insurance industry enhances actual business models and creates new ones. E-insurance refers to creating and providing insurance and connected financial services through digital solutions. In this paper the impact of IT usage and digitalization on insurance sector in the Republic of Serbia is analysed. The aim of the proposed analysis is to reveal the determinants of the adoption of innovative technological solutions in insurance in the Republic of Serbia. Relying on the TOE framework, three groups of factors influencing the adoption of IT in e-insurance are identified: technological, organizational and environmental. Panel data approach and logistic regression are used to examine the effects of proposed factors on e-insurance adoption. The obtained results indicate that organizational and environmental factors have statistically significant influence on the achieved level of e-insurance adoption, while only the market share of the insurance company positively influences the odds of e-insurance adoption. Therefore, it can be concluded that e-insurance in the Republic of Serbia is the matter of reputation and tendency of insurers to achieve short-term gains and a competitive advantage through innovation.
Keywords: L86; L81; G22; C33; M15; O33; 330; digital transformation; insurance; e-services; e-insurance; technology adoption; TOE framework; panel analyses